Chondroectodermal dysplasia (Ellis-van Creveld syndrome) - Singh, Om Prakash; Kumar, Vikas; Kumar, Rahul (International Journal of Contemporary Pediatrics, 2021)
Ellis-van Creveld syndrome (EVC) is a very rare mesenchymal- ectodermal dysplasia. This was first described in 1940 by Richard W. B. Ellis and Simon van Creveld.This rare condition is inherited as an autosomal recessive trait with variable expression. It is also known as mesoectodermal dysplasia or chondroectodermal dysplasia. The main features of this syndrome are short ribs, polydactyly, growth retardation, and ectodermal and heart defects. It is a rare disease with approximately 150 cases reported worldwide. It was found to be more common among the Amish. But sporadic cases have been reported from all over the world including India. The generalized dysplasia of endochondral ossification is because of in a novel gene on chromosome 4p16. Mutations of the EVC1 and EVC2 genes, located in head to head configuration on chromosome 4p16 have been identified as a causative factor